Microelectrochemical investigation of anodic oxide formation on the aluminum alloy AA2024. (20th September 2017) - Schneider, M.; Liebmann, T.; Langklotz, U.; Michaelis, A.
Abstract: The present paper deals with the influence of the most relevant intermetallic phases (S- and Θ-phases) of the aluminum alloy AA2024 under anodizing conditions in citric acid. The study is a combinatorial approach of localized microelectrochemistry and complementary material diagnostic using SEM/EDX-analysis. The EDX-analysis is carried out quantitatively. It is shown that different individual electrochemical processes, e.g. anodic oxide formation and corrosion effects, superimpose and dominate the anodizing process at different time scales. The complexing effect of citric acid on copper can be excluded at the chosen acidic pH value. Though, the formation of obviously dense barriers such as oxide films leads to a oxidation behavior in citric acid similar to the anodizing in neutral electrolytes.